Analytic methods for assessing joint exposure effects of preterm birth and neighborhood deprivation on first grade academic outcomes among Georgia public school children / Jennifer L. Richards & Michael R. Kramer. - Richards, Jennifer L.; Kramer, Michael R. (Sage Publications Ltd, 2017)
This case study presents an example of assessing additive interaction to analyze joint exposure effects using a study that we conducted to assess the effects of preterm birth and neighborhood deprivation on Georgia public school children's risk of failing their first grade statewide standardized tests in mathematics. We first discuss basic principles of additive versus multiplicative interaction and instruct readers to carefully consider which interaction scale is appropriate for their analyses. Then, we demonstrate the calculation of risk differences for a binary outcome from an interaction model and provide guidance on presentation of interaction results.